2012
DOI: 10.1017/s0967199412000019
|View full text |Cite
|
Sign up to set email alerts
|

Development of interspecies cloned embryos reconstructed with rabbit (Oryctolagus cuniculus) oocytes and cynomolgus monkey (Macaca fascicularis) fibroblast cell nuclei

Abstract: Interspecies somatic cell nuclear transfer (ISCNT) has been proposed as a technique to produce cloned offspring of endangered species as well as to investigate nucleus-cytoplasm interactions in mammalian embryo. However, it is still not known which embryo culture medium is optimal for ISCNT embryos for the nuclear donor or the oocyte recipient. We assessed the effects of the culture medium on the developmental competence of the ISCNT embryos by introducing cynomolgus monkey (Macaca fascicularis) fibroblast nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The in vitro development of iSCNT embryos was also reported to vary with the in vitro culture (IVC) medium used for culturing the embryos (Liu et al, 2004). It still remains uncertain whether donor-specific or recipient-specific embryo culture medium may be suitable for optimal in vitro development of iSCNT embryos (Chang et al, 2003;Yamochi et al, 2012;Yang et al, 2003;Zhao et al, 2007). Amaranth et al (2011b) observed that pig embryo culture medium could support in vitro development of mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro development of iSCNT embryos was also reported to vary with the in vitro culture (IVC) medium used for culturing the embryos (Liu et al, 2004). It still remains uncertain whether donor-specific or recipient-specific embryo culture medium may be suitable for optimal in vitro development of iSCNT embryos (Chang et al, 2003;Yamochi et al, 2012;Yang et al, 2003;Zhao et al, 2007). Amaranth et al (2011b) observed that pig embryo culture medium could support in vitro development of mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…iSCNT, on the other hand, has been considered a good alternative: NHP research can be costly, and using cytoplasm from other well-studied species can reduce costs. For either SCNT or iSCNT, different media have been tested; HECM (Rhesus macaque SCNT: [ 153 ]); SOF (Crab-eating macaque iSCNT: [ 154 ]); CMRL-1066 and M199 (Cynomolgus macaque iSCNT: [ 29 ]). In 2006, Zhou et al used HECM as primate SCNT embryo culture medium in their work to compare two SCNT methods in rhesus monkeys [ 153 ].…”
Section: Introductionmentioning
confidence: 99%
“…In macaques in general, the most suitable culture condition for these iSCNT embryos is not yet clear, but this study suggests that the medium is crucial, while oxygen and temperature during culture may not be as important in this species [ 28 ]. The research performed by Yamoshi et al (2013) tested rabbit cytoplasts as recipients for cynomolgus monkey nuclei [ 29 ] and used culture media previously studied for rabbit embryo production in vitro, but optimized for this macaque [ 156 ]. This research group found that the blastocyst rate was clearly improved when using mCMRL-1066 (17%) compared to M199 media (0%, all embryos arrested at 4 cells).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspecies somatic cell nuclear transfer (iSCNT) has been developed for the purpose of endangered animal conservation (Thongphakdee et al ) as well as for analyzing the interactions between the donor nucleus and the recipient cytoplasm (Yamochi et al ); however, incomplete nuclear reprogramming, a low blastocyst rate, and abnormal epigenetic reprogramming are still major problems of this technique (Shi et al ).…”
Section: Introductionmentioning
confidence: 99%